Establishment of Primary Adult Skin Fibroblast Cell Lines from African Savanna Elephants (Loxodonta africana) - Amèlia Jansen van Vuuren; Julie Bolcaen; Monique Engelbrecht; Willem Burger; Maryna De Kock; Marco Durante; Randall Fisher; Wilner Martínez-López; Xanthene Miles; Farzana Rahiman; Walter Tinganelli; Charlot Vandevoorde (Animals, 2023)
Following population declines of the African savanna elephant (Loxodonta africana) across the African continent, the establishment of primary cell lines of endangered wildlife species is paramount for the preservation of their genetic resources. In addition, it allows molecular and functional studies on the cancer suppression mechanisms of elephants, which have previously been linked to a redundancy of tumor suppressor gene TP53. This methodology describes the establishment of primary elephant dermal fibroblast (EDF) cell lines from skin punch biopsy samples (diameter: ±4 mm) of African savanna elephants (n = 4, 14–35 years). The applied tissue collection technique is minimally invasive and paves the way for future remote biopsy darting. On average, the first explant outgrowth was observed after 15.75 ± 6.30 days. The average doubling time (Td) was 93.02 ± 16.94 h and 52.39 ± 0.46 h at passage 1 and 4, respectively. Metaphase spreads confirmed the diploid number of 56 chromosomes. The successful establishment of EDF cell lines allows for future elephant cell characterization studies and for research on the cancer resistance mechanisms of elephants, which can be harnessed for human cancer prevention and treatment and contributes to the conservation of their genetic material.